Analisis Sarana Kohesi Leksikal dalam Teks Berita Humas di Website Kanwil Kemenag Jawa Tengah - Khoirul Anam; Hermintoyo Hermintoyo; Sri Puji Astuti (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
This research is descriptive qualitative. The method of providing data used is the library method, using listening, reading, and note-taking techniques. The data source was obtained from the news text of the Central Java Ministry of Religion Regional Office's online news site. As a research in the form of a library method, the data sources of this study took six news texts that were considered representative. The text criteria selected as data sources are news texts that contain the use of cohesion and are limited to news related to leadership activities within the Regional Office of the Ministry of Religion of Central Java which will take place in 2021. This study uses discourse analysis that focuses on cohesion. The results of this study are the use of lexical cohesion in the text. The use of means of lexical cohesion include repetition, synonymy, antonym, collocation, hyponymy, and equivalence. The means of lexical cohesion in the text used by the author function to emphasize the stressed word, clarify the meaning of the sentence, and achieve the aspect of discourse cohesion.